The Would-Be Author : Molière and the Comedy of Print - Call, Michael, 1976- (Book collections on Project MUSE., 2015)
Michael Call's The Would-Be Author is the first full-length study to examine Moliere's evolving - and at times contradictory - authorial strategies as evidence both by his portrayal of authors and publication within the plays and by his own interactions with the seventeenth-century Parisian publishing industry. Historians of the book have described the time period that coincides with Moliere's theatrical activity as centrally important to the development of authors' rights and to the professionalization of the literary field. A seventeenth-century author, however, was not so much born as negotiated through often-acrimonious relations in a world of new and dizzying possibilities. The learning curve was at times steep and unpleasant, as Moliere discovered when his first Parisian play was stolen by a rogue publisher. Nevertheless, the dramatist proved to be a quick learner: from his first published play in 1660 until his death in 1673, Moliere changed from a reluctant and victimized author to an innovator (or, according to his enemies, even a swindler) who aggressivley secured the rights to his plays - stealing them back when necessary - and acquired for himself publication privileges and conditions relatively unknown in an era before copyright. As Moliere himself wrote, making people laugh was "une etrange entreprise" (La Critique de L'École des femmes, 1663). To an even greater degree, comedic authorship for the playwright was a constant work in progress, and in this sense, "Moliere" - the stage name that became a pen name - represents the most carefully elaborated of Jean-Baptiste Poquelin's invented characters. -- from back cover.